Studies of operational variables in batch mode for genetically engineered Escherichia coli cells containing penicillin acylase - Bhattacharya S.; Gupta V.S.; Prabhune A.A.; SivaRaman H.; Debnath M.; Ranjekar P.K. (My University, 2025)
A recombinant Escherichia coli was constructed by cloning the penicillin acylase gene from E. coli itATCC 11105. The cloning was carried out using a recombinant plasmid pUSAD2 harboring the pac gene. The recombinant E. coli DH 5 cells were used as a biocatalyst and were studied in a batch reactor for determination of optimum value for some of the process parameters, such as effect of pH, temperature, substrate concentration, kLa and effect of carbon and nitrogen source on penicillin acylase production. These values were then compared with the values obtained with the standard parent strain. Whereas the cloned pac gene was found to produce higher levels of penicillin acylase constitutively, the process parameters remained about the same for both the parent and the recombinant. © 1993.